MOTIVASI INTRINSIK DAN EKSTRINSIK SERTA PENGARUHNYA TERHADAP KINERJA KARYAWAN (STUDI PADA PEKERJA PT PERTAMINA RU V BALIKPAPAN) - Amir, Rani Lupita; Azzuhri, Misbahuddin (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2015)
The purpose of this research is to test implication of motivation intrinsic and motivation extrinsic to employee performance and to determine which variables dominant to employee performance. This research was conducted in PT PERTAMINA RU V (persero) and using simple random probability sampling which generate in 100 respondents. Type of research used in this research is explanatory research. Simultaneously the influence of intrinsic motivation and extrinsic motivation on employee performance is significant and positive. Partially, intrinsic motivation significantly influence employee performance, whereas extrinsic motivation no significant effect on the performance of the employee. In this research also found that the dominant influence intrinsic motivation rather than extrinsic motivation on employee performance. Keywords: intrinsic motivation, extrinsic motivation, employee performance.